Systematic review: Teacher intervention strategies for students with special needs in bullying situations - Tremblay, Kelly; Poulin, Marie-Hélène; Guimond, Fanny-Alexandra (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2022)
Bullying in primary schools is a concern, especially for students with special needs. Despite the implementation of preventative programmes, teachers are lacking intervention strategies. This review focuses on teachers’ interventions in bullying situations experienced by students with special needs and their effects on bullying and victimization rates. Four databases were searched for a total of 417 articles. Ten of these articles (2008 to 2019) were selected and none report results specific to students with special needs. Teachers prioritize strategies that are not supported by research, such as punishment. The results are discussed in relation to research and real-live needs.